Pendidikan Dan Latihan Guru Untuk Meningkatkan Pemeliharaan Kesehatan Gigi Dan Mulut Di SLB YBSM - Zahara, Elfi; Andriani; Intan Liana (Poltekkes Kemenkes Aceh, 2022)
Children need strong and healthy teeth not only to chew food but also to pronounce words. Dental care from an early age is an important step for healthy children's teeth. Children with special needs are children with special characteristics that are different from children in general without always showing mental, emotional, or physical incapacity. SLB YBSM Banda Aceh is a foundation that specifically accommodates people with disabilities. Based on interviews with school principals where the children are deaf, physically disabled, and blind (Tuna Graphite). This community service aims to improve actions on how to brush teeth properly and correctly and reduce dental and oral hygiene status in children. at the SLB YBSM Lamjabat Banda Aceh City. This community service was carried out using a descriptive method, with the target of 30 teachers and students as respondents at the YBSM Special School in Banda Aceh City. The intervention provided was in the form of training and demonstration of how to brush teeth properly and correctly. Keywords: Education and maintenance of dental and oral health